Chained Animation: Collaborative Forms of Filmmaking in Education. (July 2022) - Hagler, Juergen; Rauscher, Remo
This article discusses experimental forms of collaborative filmmaking in education and introduces the pedagogical concept of Chained Animation. Animation filmmaking usually involves teamwork; production pipelines are traditionally linear and hierarchically structured, separated into direction (or artistic direction) and production teams. By contrast, Chained Animations are non-linear and based on a large group of animators working together at various levels. This concept is particularly well suited to education as it integrates all participants equally, from the idea phase all the way through to its realization. In addition to teaching basic animation principles, this experimental form of education goes beyond established methods of practising those principles. The educational concepts for Chained Animations follow different strategies and range from professional workflows to playful, experimental forms that emphasize participatory and collaborative aspects within large groups. In this article, the authors first examine participatory art practices; then they discuss experimental forms of collaboration in animation and education, using examples from art, film and science. This article examines different experimental approaches, challenges and findings, which are based on three case studies undertaken at the University of Applied Sciences Upper Austria, Hagenberg Campus – Home (2016), Utopia Now (2017) and Draft One (2018) – ultimately presenting guidelines for Chained Animation in education.